THE INFLUENCE OF THE DIMENSIONS OF TOTAL QUALITY MANAGEMENT TOWARDS EMPLOYEE PERFORMANCE IN RSUD DR. H. ISHAK UMARELLA - Ralahallo, Fransiska Natalia; Titioka, Baretha Meisar; Ririhatuela, Elisabeth M P (Pattimura University, 2023)
Introduction/Main Objectives: To analyze the influence of the dimensions total quality management toward employee performance in an Indonesian Regional Public Hospital (RSUD) Dr. H. Ishak Umarella. Background Problems: This research is conducted based on the premise that there are problems related to employee performance at RSUD Dr. H. Ishak Umarella which were inconsistent throughout 2020. According to the condition, the objective of this research is to verify the influence of total quality management toward employee performance. Novelty: In the dimensions of total quality management used, in which there are additional dimensions and adjustment to the dimensions used according to the object of research. Research Methods: The process of sampling applied in this research is purposive sampling, using the total of 100 respondents. Data are collected using questionnaires as the main instrument and Likert Scale to measure respondents' answers in the questionnaires. Finding/Results: The result shows that the focus on customer variable (X1), employee engagement and empowerment variable (X2), continuous improvement variable (X3), teamwork variable (X4), and education and training variables (X5) have a positive and significant influence towards employee performance (Y) at RSUD Dr. H. Ishak Umarella. Conclusion: This research concludes that in an effort to improve the performance of its employees, every government agency must attend to and strengthen the five variables